Augmented Reality Users: The Effect of Perceived Ease of Use, Perceived Usefulness, and Customer Experience on Repurchase Intention - Nurul Anifa; Sanaji Sanaji (Journal of Business and Management Review, 2022)
E-commerce comes from presenting product catalogs through two-dimensional static images that create limitations for users. Augmented reality features on smartphones have changed online consumer shopping activities. This allows consumers to try various cosmetic product variants virtually anywhere and anytime. Augmented reality is a new technology that provides convenience and experience for customers online to buy cosmetics online and try products without having to remove makeup. This study aims to examine the effect of independent variables on a dependent variable, with mediating variables. The population of this study is users of the virtual product trial feature who have purchased cosmetic products online aged 17–50 years in Indonesia, with a sample of 200 respondents. This research used path analysis, with the results showing that perceived ease of use affects trust, customer experience affects customer satisfaction, perceived usefulness, and customer satisfaction affects repurchase intention. However, trust does not affect repurchase intention. Based on these results, it is recommended that companies that provide product trial features adopt augmented mobile reality to pay attention to the convenience and benefits and improve the quality of the shopping experience.